Applicability of different types of patient records for patient recruitment systems - Schreiweis, Björn; Bergh, Björn (MEDINFO 2015: eHealth-enabled health ; Part 2, 2015)
Patient records--types of Electronic Medical Records--are implemented to support patient recruitment. Different types of patient records have not yet been analyzed as to the number of Patient Recruitment System requirements can be found in each type of patient record. According to our analysis, personal electronic health records (PEHRs) tend to allow for most requirements to be found.